Collagen Gene Polymorphisms Previously Associated with Resistance to Soft-Tissue Injury Are More Common in Competitive Runners Than Nonathletes - Shane Heffernan (Journal of Strength and Conditioning Research, 2023)
Dines, HR, Nixon, J, Lockey, SJ, Herbert, AJ, Kipps, C, Pedlar, CR, Day, SH, Heffernan, SM, Antrobus, MR, Brazier, J, Erskine, RM, Stebbings, GK, Hall, ECR, and Williams, AG. Collagen gene polymorphisms previously associated with resistance to soft-tissue injury are more common in competitive runners than nonathletes. J Strength Cond Res XX(X): 000–000, 2022—Single-nucleotide polymorphisms (SNPs) of collagen genes have been associated with soft-tissue injury and running performance. However, their combined contribution to running performance is unknown. We investigated the association of 2 collagen gene SNPs with athlete status and performance in 1,429 Caucasian subjects, including 597 competitive runners (354 men and 243 women) and 832 nonathletes (490 men and 342 women). Genotyping for COL1A1 rs1800012 (C > A) and COL5A1 rs12722 (C > T) SNPs was performed by a real-time polymerase chain reaction. The numbers of “injury-resistant” alleles from each SNP, based on previous literature (rs1800012 A allele and rs12722 C allele), were combined as an injury-resistance score (RScore, 0–4; higher scores indicate injury resistance). Genotype frequencies, individually and combined as an RScore, were compared between cohorts and investigated for associations with performance using official race times. Runners had 1.34 times greater odds of being rs12722 CC homozygotes than nonathletes (19.7% vs. 15.5%, p = 0.020) with no difference in the rs1800012 genotype distribution (p = 0.659). Fewer runners had an RScore 0 of (18.5% vs. 24.7%) and more had an RScore of 4 (0.6% vs. 0.3%) than nonathletes (p < 0.001). Competitive performance was not associated with the COL1A1 genotype (p = 0.933), COL5A1 genotype (p = 0.613), or RScore (p = 0.477). Although not associated directly with running performance among competitive runners, a higher combined frequency of injury-resistant COL1A1 rs1800012 A and COL5A1 rs12722 C alleles in competitive runners than nonathletes suggests these SNPs may be advantageous through a mechanism that supports, but does not directly enhance, running performance.